Characterizing the Limits of Magnetic Resonance Imaging Near Metallic Prostheses - Smith, Matthew R. (Magn Reson Med, 2014)
PURPOSE: To characterize the fundamental limits of MRI near metallic implants on RF excitation, frequency encoding, and chemical shift-encoding water-fat separation. METHODS: Multicomponent 3D digital models of a total hip and a total knee replacement were used to construct material specific susceptibility maps. The fundamental limits and spatial relationship of imaging near metallic prostheses were investigated as a function of distance from the prosthetic surface by calculating 3D field-map perturbations using a well-validated k-space based dipole kernel. RESULTS: Regions limited by the bandwidth of RF excitation overlap substantially with those fundamentally limited by frequency encoding. Rapid breakdown of water-fat separation occurs once the intra-voxel off-resonance exceeds ~6 ppm over a full range of fat-fractions (0 to 100%) and SNR (5-100). CONCLUSION: Current 3D multispectral imaging methods would not benefit greatly from exciting spins beyond ±12 kHz despite the presence of signal that lies outside of this range from tissue directly adjacent to the metallic implants. Methods such as phase encoding in all three spatial dimensions are necessary to spatially resolve spins beyond an excitation bandwidth of ±12 kHz. The approach described in this work provides a benchmark for the capabilities of current imaging techniques to guide development of new MRI methods for imaging near metal.